Current outcomes of myringoplasty in a European referral children's hospital. (September 2022) - Bruno, Chiara; Guidi, Mariapaola; Locatello, Luca Giovanni; Gallo, Oreste; Trabalzini, Franco
Abstract: Objectives: Myringoplasty is a frequently performed procedure in children, with a heterogeneous failure rate. Our study aimed to evaluate the outcome of myringoplasty in a pediatric hospital and to identify which are risk factors for reperforation or poor hearing improvement after surgery. Methods: Preoperative and intraoperative variables between pediatric patients who had undergone myringoplasty with an intact tympanic membrane at follow-up and the cases with reperforation were compared. The same factors were investigated as potential predictors of audiological success. Pre and postoperative PTA and ABG were compared in the whole population, in structural success and failure groups and closure of ABG was calculated and used to compare the audiological outcomes between the two groups. Results: Parameters that affected the postoperative integrity of TM were age, the time between diagnosis and surgery, the intraoperative status of the middle ear, and secondhand smoke exposure. Early perforations occurred mostly after surgeries performed by trainees, while late perforations were more frequently in autumn. Myringoplasty, regardless of the structural outcome, can improve the ABG and PTA. No preoperative and intraoperative parameters affected the audiological outcome. Conclusion: Pediatric myringoplasty is a safe and successful procedure that can improve hearing, regardless of the structural outcome. In light of our results, parameters to consider before surgery are age, the time between diagnosis and surgery, the intraoperative status of the middle ear, and secondhand smoke exposure. Highlights: Today there is no consensus on when to perform myringoplasty and what factors influence its outcomes in children. Age, time between diagnosis and surgery, intraoperative status of the middle ear, and secondhand smoke exposure influence the outcome. Early perforations occur mostly after surgeries performed by trainees, while late perforations are more frequently in autumn. Myringoplasty can improve the ABG and PTA. No preoperative and intraoperative parameters affect the audiological outcome.